Addressing school violence from the perspective of parents/family (Research, Society and Development, 2022)
Objective: To analyze perceptions about coping with school violence from the point of view of parents/family members of students at a State school in the City of Recife. Methodology: The qualitative method was used, with data collected through interviews with a previously structured script and evaluated based on content analysis. Results: Five categories emerged from the interviewees' discourse, namely: School violence in the students' parents' imagination; reason for the occurrence of school violence; the aggression suffered and practiced by the children at school; the reflection of school violence on parents' lives and the confrontation of school violence. For the family, school violence is multifaceted and has several responsible, among them the family itself, students, faculty, among others. The interviewees cite that one of the main reasons for violence at school is the lack of domestic education, but they also did not exclude the lack of “a firm pulse on the part of the teaching staff” and still believe that working together with the family and the school can minimize the problem. Conclusion: The results showed the importance of the bond between the family and the school, and that this bond can have a great impact on combating violence in the school space.